2018
DOI: 10.1038/s41419-018-0426-z
|View full text |Cite|
|
Sign up to set email alerts
|

Activated dendritic cells modulate proliferation and differentiation of human myoblasts

Abstract: Idiopathic Inflammatory Myopathies (IIMs) are a heterogeneous group of autoimmune diseases affecting skeletal muscle tissue homeostasis. They are characterized by muscle weakness and inflammatory infiltration with tissue damage. Amongst the cells in the muscle inflammatory infiltration, dendritic cells (DCs) are potent antigen-presenting and key components in autoimmunity exhibiting an increased activation in inflamed tissues. Since, the IIMs are characterized by the focal necrosis/regeneration and muscle atro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 78 publications
(79 reference statements)
0
10
0
Order By: Relevance
“…A similar effect was observed when myoblasts and myotubes were incubated with TNF-α, IFN-γ, and, TGF-β, suggesting a role of circulating cytokines, in addition to the requirement for cell-cell contact. Moreover, co-injection of human myoblasts and DCs into freeze-injured tibialis anterior muscle of immunodeficient mice enhanced human myoblast migration, although the absolute number of human muscle fibers was unchanged (Ladislau et al, 2018), similar to what had been shown for macrophages (Bencze et al, 2012). Similarly, increased numbers of activated DCs are seen in inflamed muscle (Pimorady-Esfahani et al, 1997;Padilla and Reed, 2008;Tournadre and Miossec, 2008) suggesting that DCs may also present antigens to T cells at the site of the lesion during myositis, in addition to the classic antigen-presentation in the draining lymph nodes (Hughes et al, 2016).…”
Section: Dendritic Cells and Muscle Inflammationmentioning
confidence: 98%
“…A similar effect was observed when myoblasts and myotubes were incubated with TNF-α, IFN-γ, and, TGF-β, suggesting a role of circulating cytokines, in addition to the requirement for cell-cell contact. Moreover, co-injection of human myoblasts and DCs into freeze-injured tibialis anterior muscle of immunodeficient mice enhanced human myoblast migration, although the absolute number of human muscle fibers was unchanged (Ladislau et al, 2018), similar to what had been shown for macrophages (Bencze et al, 2012). Similarly, increased numbers of activated DCs are seen in inflamed muscle (Pimorady-Esfahani et al, 1997;Padilla and Reed, 2008;Tournadre and Miossec, 2008) suggesting that DCs may also present antigens to T cells at the site of the lesion during myositis, in addition to the classic antigen-presentation in the draining lymph nodes (Hughes et al, 2016).…”
Section: Dendritic Cells and Muscle Inflammationmentioning
confidence: 98%
“…Crotoxin, a venom PLA2, is known to modulate the function of dendritic cells [ 37 ] Dendritic cells have been associated with several autoimmune inflammatory myopathies [ 38 , 39 ]. When incubated with myoblasts in cell culture, dendritic cells are able to interact with them, inducing myoblast proliferation and migration, but inhibiting myotube differentiation [ 40 ]. Our observations stress the need to assess the role of dendritic cells in the overall processes of inflammation and muscle regeneration after venom-induced myonecrosis.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, we found that the production of pro-inflammatory cytokines (IL-6, TNF-a, and IFNb) after DNA vaccination was significantly diminished in STING -/mice but similar in control mice and mice lacking STING in cDCs (Figure 4). Plasmacytoid dendritic cells (pDCs), a DC subset that still possess STING in cDC STING cKO mice, may be a potential DC subset that is producing IFN-a/b post-DNA vaccination, which subsequently aids in CD8 + T cell effector programming (15,28). Additionally, studies suggest that DNA vaccine transfected myocytes produced some IFN-b albeit in significantly lower quantities (29) and could contribute to induction of polyfunctional CD8 + T cell responses.…”
Section: Discussionmentioning
confidence: 99%